Analysis of Women Social Entrepreneurship on Micro and Small Enterprises - Nurul Asfiah; Muslich Anshori; Imron Mawardi (Faculty of Economics and Business, University of Muhammadiyah Malang, 2018)
Small, and Medium-sized Enterprises (SMEs) are one of the main actors for national development process. This research is intending to explore the phenomenon or symptom of socio-economic problems in those SMEs. That done by observing women entrepreneur, especially social entrepreneurship subject in Micro and Small Enterprises, that become the member of economic program BUEKA. Therefore, this is a qualitative research with phenomenology approach. Data seeking is directly involved observation or Participating Observation in some of the entrepreneurship events that held by ‘Aisyiyah Movement, and thereafter record it in detail. Collecting data is done with interview about: 1) SMEs relation pattern with the companion institutions, 2) Comprehensive illustration about women empowerment in SMEs entrepreneur, 3) Activities that have been done by those women entrepreneurs are categorized as social entrepreneurship. And then, this research is completed thorough indepht interview for discovering data that is started from the key informant. The result from this research is ‘Aisyiyah is a women organization that driven to improve the life quality of women and family, with social entrepreneurship.